2021
DOI: 10.1111/isj.12336
|View full text |Cite
|
Sign up to set email alerts
|

Issues, challenges, and a proposed theoretical core of agile software development research

Abstract: Over the last two decades, agile software development (ASD) has garnered much attention in both research and practice. Several ASD methods and techniques have been developed and studied. In particular, researchers have provided several theoretical perspectives on ASD and contributed rich insights to the ASD practice. Still, despite calls for a more unified theoretical understanding of ASD, a theoretical core of ASD has not been identified. This paper offers a theoretical core of ASD research, clarifying what i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 87 publications
0
20
0
Order By: Relevance
“…But, due to lack of automation adopted by the organisation creates struggle to cope with the agile transformation Baham and Hirschheim 2021 ; Scholz et al 2020 F5 Less motivation and enthusiasm due to COVID-19 impact COVID-19 negatively affects budget, hence affects value generation adversely creating less motivation and enthusiasm Koch and Schermuly 2021 ; Malik et al 2021 F6 Projects take too long to get going Agile project implementation is hampered by indecision and also inability of organisation to take prompt decision Ragas and Ragas 2021 F7 Slow Governance processes Agile project implementation will lead into conflicts with existing systems and processes leading into slow governance Sjödin et al 2020 ; Ragas and Ragas 2021 F8 Non- availability of skilled people The emerging economies like India are lacking in skilled staff. Thus, agile project implementation is difficult if the manpower is non-skilled Koch and Schermuly 2021 ; Niederman 2021 F9 Risk mitigation Agile is more active in risk management as compared to waterfall model Sithambaram et al 2021 F10 Structural impediments A set of exiting conditions may thwart the agile project management implementation Narkhede et al 2020 F11 Lack of clarity around roles Agile project focuses on team roles that may create ambiguity in the job roles Malik et al 2021 F12 Resistance to Change Challenges are faced when exposed to the other parts of the organisation for adopting the agile projects Sithambaram et al 2021 …”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…But, due to lack of automation adopted by the organisation creates struggle to cope with the agile transformation Baham and Hirschheim 2021 ; Scholz et al 2020 F5 Less motivation and enthusiasm due to COVID-19 impact COVID-19 negatively affects budget, hence affects value generation adversely creating less motivation and enthusiasm Koch and Schermuly 2021 ; Malik et al 2021 F6 Projects take too long to get going Agile project implementation is hampered by indecision and also inability of organisation to take prompt decision Ragas and Ragas 2021 F7 Slow Governance processes Agile project implementation will lead into conflicts with existing systems and processes leading into slow governance Sjödin et al 2020 ; Ragas and Ragas 2021 F8 Non- availability of skilled people The emerging economies like India are lacking in skilled staff. Thus, agile project implementation is difficult if the manpower is non-skilled Koch and Schermuly 2021 ; Niederman 2021 F9 Risk mitigation Agile is more active in risk management as compared to waterfall model Sithambaram et al 2021 F10 Structural impediments A set of exiting conditions may thwart the agile project management implementation Narkhede et al 2020 F11 Lack of clarity around roles Agile project focuses on team roles that may create ambiguity in the job roles Malik et al 2021 F12 Resistance to Change Challenges are faced when exposed to the other parts of the organisation for adopting the agile projects Sithambaram et al 2021 …”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, agile project implementation is difficult if the manpower is non-skilled Koch and Schermuly 2021 ; Niederman 2021 F9 Risk mitigation Agile is more active in risk management as compared to waterfall model Sithambaram et al 2021 F10 Structural impediments A set of exiting conditions may thwart the agile project management implementation Narkhede et al 2020 F11 Lack of clarity around roles Agile project focuses on team roles that may create ambiguity in the job roles Malik et al 2021 F12 Resistance to Change Challenges are faced when exposed to the other parts of the organisation for adopting the agile projects Sithambaram et al 2021 F13 Lack of shared value Challenge to agile projects implementation is the shared value that occurs due to multiple teams Hoda and Murugesan 2016 ; Baham and Hirschheim 2021 F14 Skepticism towards the new way of working Skepticism is the common problem in the agile project implementation. At one hand there are benefits of agility, but on the other hand opposition to implement it Zasa et al 2020 ; Baham and Hirschheim 2021 F 15 Lack of investment The lack of funding may hamper to implement agile projects Joshi et al 2020 ; Holden et al 2021 F 16 Misunderstanding agile concepts Agile Projects needs to be implemented with concepts and planning but due to lack of clarity it sometimes misleads the project managers Sithambaram et al 2021 F 17 …”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the emphasis on promoting sustainable development to maintain a constant pace, the reality in agile ISD projects often tells a different story. By striving to enact agile values and principles, such as rapid time-boxed iterations to frequently deliver working software, permanent responsiveness to change and feedback, and open, collaborative interactions with multiple stakeholders Matook 2020, Baham andHirschheim 2021), AISDPU can place specific situational (e.g., time-, change-, and transparencyrelated) demands on developers that may carry unintended consequences. To the best of our knowledge and based on our review of the AISDPU literature (see Online Appendix A), we identified only three relevant studies that looked into the individual-level implications of AISDPU for developer stress and work exhaustion.…”
Section: Agile Isd Practices Use and Its Effectsmentioning
confidence: 99%
“…Industry reports and recent empirical findings indicate that agile ISD practices can be experienced by developers as a benefit and burden and that such experiences may fluctuate over short time intervals (Balbes 2017, Tuomivaara et al 2017. As agile ISD methods and their associated practices significantly change the structure and environment of software developers' daily work because of demanding features that emphasize fast turnaround times, responsiveness to change, and individual performance transparency (Baham and Hirschheim 2021), they may have important consequences for developers' daily appraisals and stress responses. On one day, agile ISD practices may be experienced as a challenge and "fire developers up."…”
Section: Introductionmentioning
confidence: 99%
“…In the fourth paper, Baham and Hirschheim (2022) and what is less essential for IS agility, with the intention of sparking a scholarly discussion, and providing implications of such a core for understanding method tailoring.…”
mentioning
confidence: 99%